2014
DOI: 10.1002/ente.201402070
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Calophyllum inophyllum Oil with a High Free Fatty Acid Content to Biodiesel using a Starch‐Derived Catalyst

Abstract: Biodiesel was produced from Calophyllum inophyllum oil using a starch‐derived catalyst. The catalyst, obtained by the sulfonation of carbonized starch, was characterized by various techniques. The catalyst was capable of esterification and transesterification reactions under the conditions studied and it was superior to a catalyst derived from glucose. A biodiesel yield of 99.0 % was achieved under the optimized conditions. The activity of the starch‐derived catalyst can be related to its SO3H density but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…7 Apart from the importance of starch as a substrate for the preparation of valuable products, this natural polymer or its slightly modied derivatives can be used as great tools for other purposes. [25][26][27][28][29][30][31] For example, starch with many hydroxyl groups can act like a molecular octopus with many tentacles to remove environmental pollutants such as heavy metals, 32 dyes, 33 pesticides, 34 anti-biotics, 35 and oils. 36 Also, there are many reports about starchbased material application as biodegradable and renewable alternatives for current widely used non-renewable resins.…”
Section: A Little Bit About Starchmentioning
confidence: 99%
“…7 Apart from the importance of starch as a substrate for the preparation of valuable products, this natural polymer or its slightly modied derivatives can be used as great tools for other purposes. [25][26][27][28][29][30][31] For example, starch with many hydroxyl groups can act like a molecular octopus with many tentacles to remove environmental pollutants such as heavy metals, 32 dyes, 33 pesticides, 34 anti-biotics, 35 and oils. 36 Also, there are many reports about starchbased material application as biodegradable and renewable alternatives for current widely used non-renewable resins.…”
Section: A Little Bit About Starchmentioning
confidence: 99%
“…The sunflower oil was converted to biodiesel using alumina/silica supported K 2 CO 3 , under the conditions of 120 °C, 2 wt.% catalyst, and 1: 30 molar ratio [17] . The CIO was transesterified to biodiesel using starch derived catalyst at 180 °C in 5 hrs and obtained a biodiesel yield of 81 % [18] . In one of the reports, functionalized SBA‐15 supported lipase found to be a good catalyst for biodiesel synthesis under the conditions of 35 °C, 1 : 6 molar ratio in 6 hrs duration and the authors obtained a biodiesel yield of 94 % [11] .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also identified various drawbacks of using homogeneous acid catalyzed esterification such as the formation of water as a by-product and very slow reaction kinetics, compared to traditional transesterification (Gui et al, 2008). There are other diverse types of catalysts which could be employed in esterification of high FFA oils (Ayodele and Dawodu, 2014;Fang et al, 2013) but this study focuses on solid acid impregnated catalysts, particularly heteropoly acids (HPAs), because of their innate chemical resistance to moisture (Sharma et al, 2011). Also, HPAs can convert feedstock containing high amount of FFAs, which enables their use with low cost feedstocks such as used cooking oil and other non-edible vegetable oils (Endalew et al, 2011).…”
Section: Introductionmentioning
confidence: 99%